The Methodological Recommendations for Improving the Management of Enterprise Competitiveness in the Service Sector - Osypenko Stanislav M. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
The relevance of the problem of managing the competitiveness of service sector enterprises in modern conditions of economic management is determined. In a contentual form, the task of managing the competitiveness of enterprises is formulated and a scheme of its implementation is proposed, which includes the following stages: formation of factors that determine competitiveness; substantiation of the competitiveness indicator and its model; computing the competitiveness indicator and its subsequent factor analysis; determination of reserves for growth of the competitiveness index; formation of the task of increasing competitiveness; formation of a list of measures for implementing the task; selection of measures for the implementation; implementation of measures, control and regulation. The procedure for computing the integral indicator of competitiveness, which includes groups of indicators that determine the state of the enterprise and the competitiveness of its products, as well as indicators within each group, is considered. The methodology of economic analysis of the level of competitiveness of the enterprise is proposed, which allows to conduct an overall assessment of its competitive position compared to competitors; determine the influence of factors on the difference in their position from the position of competitors; calculate the reserves of growth of the competitiveness indicator and develop measures for their implementation. In accordance with the competitive strategy of the enterprise and the task of increasing the competitiveness indicator on the basis of the use of the provisions of the theory of economic efficiency, a list of measures is substantiated, the practical implementation of which will allow to perform the task with a minimum amount of resources. Operational control over the implementation of measures and their impact on the competitiveness indicator is envisaged in order to make corrective managerial decisions in a timely manner.